The Palgrave Handbook of Global Rehabilitation in Criminal Justice - Vanstone, Maurice; Priestley, Philip (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"From Fiji to Finland, Uruguay to the USA, this fascinating collection of authors and essays provides the most comprehensive and up-to-date portrait of the state of rehabilitation around the world today." - Shadd Maruna, Professor of Criminology, Queen's University Belfast, UK and President of the American Society of Criminology This handbook provides a unique overview of rehabilitation as practiced internationally in criminal justice. Through the contributions of a diverse group that includes, among others, academics (some of whom are former practitioners), research students, a judge, and a probation chief, it reflects common features of criminal justice in different countries and documents their diversity and celebrates their vitality. In recent times the idea of 'law and order' has been expropriated by populist, authoritarian and doctrinaire regimes, almost always and nearly everywhere in the service of arbitrary and unjust rule. By and large this handbook does not include such regimes. But 'law' itself also has the capacity to constrain rulers, and 'order' in the form of social peace is a universally approved civic asset. In part, the book provides a counter-narrative demonstrating that although criminal justice dispositions such as probation, prisons, and parole can be represented as a 'via dolorosa', rehabilitation as illustrated in these pages can become a journey that leads by degrees towards the possibility of a better life. The handbook will be of interest to students, academics, practitioners, managers, policy makers and all those who wish to gain insight into the why and the how of rehabilitation in criminal justice systems across the world. Maurice Vanstone is Emeritus Professor of Criminology and Criminal Justice at Swansea University, UK. He is the author of Supervising Offenders in the Community: A History of Probation Theory and Practice (2004) and co-editor (with Philip Priestley) of Offenders or Citizens? Readings in Rehabilitation (2010). Philip Priestley is a former probation officer, academic and author of Victorian Prison Lives (1985). He has directed thirty broadcast films for UK television, including Video Letters (BBC 2 1991); Prix Europa, Berlin. He helped start services to victims and probation day centres as alternatives to prison. He is co-editor (with Maurice Vanstone) of Probation and Politics (2016).
1. Prospect -- 2. Law, Economic Crisis, and Diversity. An Overview of Rehabilitation in Argentina -- 3. Rehabilitation and Beyond in Settler Colonial Australia: Current and Future Directions in Policy and Practice -- 4. Exploring Expectations and Realities of Rehabilitation in the Canadian Context -- 5. History and transformations of the model of rehabilitation in the criminal justice system in Chile -- 6. Rehabilitation in a Risk Society: 'The Case of China' -- 7. Penitentiary System in Colombia -- 8. Rehabilitation practices in the Adult Criminal Justice System in England and Wales -- 9. Blending Culture, Religion, and the Yellow Ribbon Program: Rehabilitation in Fiji -- 10. Rehabilitation Aims and Values in Finnish (and Nordic) Criminal Justice -- 11. Executive managerialism, frantic law reform, but desistance culture -- 12. Rehabilitation in Ghana: Assessing Prison Conditions and Effectiveness of Interventions for Incarcerated Adults -- 13. Approaches to Rehabilitation in Hong Kong -- 14. From need-based to control-based rehabilitation: the Hungarian case -- 15. A critical commentary on rehabilitation of offenders in India -- 16. Beyond the treatment paradigm: Expanding the rehabilitative imagination in rehabilitation in Ireland -- 17. Serving a Sentence in Italy: Old and New Challenges -- 18. Community-based rehabilitation in Japan: Some unique -- 19. Criminal rehabilitation in Kenya: opportunities and pitfalls -- 20. Framing and reframing rehabilitation in criminal justice in Latvia -- 21. Criminal Justice Rehabilitation in Macao, China: Suspended citizenship -- 22. The legal flaws and material implementation gaps of Mexico's rehabilitation paradigm -- 23. Rehabilitation within the Criminal-Legal System in Missouri -- 24. Resocialisation and re-integration in the Netherlands: political narrative versus reality -- 25. Rehabilitation, Restoration and Reintegration in Aotearoa New Zealand -- 26. An overview of rehabilitation mechanisms in Nigeria's criminal justice system -- 27. Penal welfarism and rehabilitation in Norway: ambitions, strengths and challenges -- 28. Rehabilitation in Romania - the first 100 years -- 29. Rehabilitation of Offenders in the Scottish Criminal Justice System -- 30. Offender Rehabilitation Approaches in South Africa: An Evidence Based Analysis -- 31. Rehabilitation in Spain: between legal intentions and institutional limitations -- 32. Criminal Justice Rehabilitation in Sweden. Towards an Integrative Model -- 33. Rehabilitation in Taiwan -- 34. Rehabilitation and the Adult Correctional Population in Texas -- 35. Key Practices in Thai Prisons: Rehabilitation -- 36. Probation and the prevention of recidivism in Tunisia: still uncertain beginnings -- 37. The unfinished symphony: progress and setbacks towards a rehabilitation policy in Uruguay -- 38. Re-entry and Reintegration in Virginia, U.S -- 39. Retrospect.
Keywords: Criminal behavior; Corrections; Punishment; Crime-Sociological aspects; Clinical psychology; Rehabilitation; Mentally ill-Rehabilitation.; Social service; Criminal law; Criminal Behavior; Prison and Punishment; Crime and Society; Rehabilitation Psychology; Social Work; Criminal Law and Criminal Procedure Law